EXPERIMENTAL ANALYSIS OF THE BEHAVIOR OF CAPPING BEAMS ACROSS THE PILES IN LOOSE SAND - Nemanja Bralović; Iva Despotović; Danijel Kukaras (Facta Universitatis. Series: Architecture and Civil Engineering)
The test program was conducted on 1G models capping beams over the tops of the group of 2x2 piles, the purpose of which was to reduce the settlement of the structure. The test program included six experiments, three of which were conducted on capping beams without piles and three on capping beams across the tops of the piles, with pile distances 3d, 4d and 5d, where d is the pile diameter and the pile length is 40 d. Test results show that the current conventional approach to the design of capping beams across the tops of the piles, where the entire load is entrusted to the piles, is too conservative and irrational. Instead, it is more economical to apply a low bearing capacity factor for piles as settlement reducers and maximize use of raft bearing capacity to carry part of the external load.